Glass ceramic, preparation method, glass ceramic product and electronic equipment
Patent Information
- Application Number
- CN202380053587.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-04-21
- Publication Date
- 2025-03-14
AI Technical Summary
The mechanical strength of existing glass cannot meet users' high requirements for resistance to drops and scratches on electronic devices.
By introducing alkali metal and alkaline earth metal components into the calcium-aluminum binary system, the glass-forming properties of the glass-ceramics are improved, the glass-forming area of the calcium-aluminate glass is expanded, and crystallized glass with higher mechanical strength is prepared.
It achieves higher drop and scratch resistance of crystal-ceramic glass, lowers the glass melting temperature and reduces energy consumption.
Smart Images

Figure CN119630615A_ABST
Abstract
Description
Glass-ceramics, preparation method, glass-ceramics products and electronic equipment
[0001] This application claims priority to the Chinese patent application filed with the China Patent Office on July 12, 2022, with application number "202210822084.1" and application name "Microcrystalline glass, preparation method, microcrystalline glass products and electronic equipment", all of which are incorporated by reference into this application. Technical Field
[0002] The present application relates to the technical field of microcrystalline glass preparation, and in particular to microcrystalline glass, preparation methods, microcrystalline glass products and electronic equipment. Background Art
[0003] In recent years, with the rapid development of electronic devices, people's demands for their drop resistance have become increasingly stringent. For example, with the continuous increase in screen size and cover size of mobile phones, and the increasing use of 3D glass, consumers have higher demands for glass's drop and scratch resistance. Therefore, a glass-ceramic with higher mechanical properties is needed to meet user needs.
[0004] Summary of the Invention
[0005] In view of this, the present application provides a microcrystalline glass, a preparation method, a microcrystalline glass product and an electronic device to provide microcrystalline glass that is more resistant to falling and scratching, thereby solving the problem that the mechanical strength of existing glass cannot meet user needs.
[0006] Some embodiments of the present application provide a glass-ceramic. The present application is described below from multiple aspects, and the embodiments and beneficial effects of the following aspects can be referenced with each other.
[0007] In a first aspect, the present application provides a microcrystalline glass, which comprises the following components, calculated in molar percentage of oxides: Al2O3: 30%-55%; CaO: 25%-55%; alkaline earth metal oxides: 8%-20%; alkali metal oxides: 3%-15%; B2O3: 0%-10%; and Sb2O3: 0%-1%.
[0008] According to the glass-ceramics of the present application, during the preparation process of the glass-ceramics, by introducing components such as alkali metals and alkaline earth metals into the calcium-aluminum binary system, its glass-forming properties can be improved, and the glass-forming region of the calcium-aluminate glass can be expanded, resulting in calcium-aluminate glass. This calcium-aluminate glass has higher mechanical strength and is more resistant to drops and scratches than traditional silicate glass and high-aluminate glass. Furthermore, the glass-melting temperature can be lowered, thereby reducing energy consumption.
[0009] As an embodiment of the first aspect of the present application, the alkaline earth metal oxide includes one or more of MgO, SrO and BaO.
[0010] As an embodiment of the first aspect of the present application, the alkaline earth metal oxide includes at least two of MgO, SrO, and BaO, and the content of each alkaline earth metal ion is 2% to 10% by mole percentage. The addition of the alkaline earth metal component can effectively improve the glass-forming properties of the calcium-aluminum binary system and increase the hardness of the glass-ceramic.
[0011] As an embodiment of the first aspect of the present application, the alkali metal oxide includes one or more of Li2O, Na2O and K2O.
[0012] As an embodiment of the first aspect of the present application, the alkali metal oxide comprises, by mole percentage of each component, 1%-10% Li2O, 2%-10% Na2O, and 0-10% K2O. This composition ratio further improves the glass-forming properties of the calcium-aluminum binary system.
[0013] As an embodiment of the first aspect of the present application, the microcrystalline glass includes nanocrystalline particles, and the nanocrystalline particles can be one or more crystal phases of CaAl2O4, MgAl2O4 and SrAl2O4.
[0014] As an embodiment of the first aspect of the present application, the average particle size of the nanocrystalline particles is 1-100 nm.
[0015] As an embodiment of the first aspect of the present application, the content of nano-crystal particles accounts for more than 50% of the total amount of the entire microcrystalline glass.
[0016] As an embodiment of the first aspect of the present application, the average particle size of the nano-microcrystalline particles is 1-50nm, and the content of the nano-microcrystalline particles accounts for more than 80% of the total amount of the microcrystalline glass. The increase in the content of the nano-microcrystalline particles can effectively improve the hardness of the microcrystalline glass.
[0017] As an embodiment of the first aspect of the present application, the Vickers hardness of the microcrystalline glass is between 8.4-9.1 GPa.
[0018] As an embodiment of the first aspect of the present application, the Young's modulus of the glass-ceramics is between 110-129 GPa.
[0019] In a second aspect, the present application also provides a method for preparing glass-ceramics, comprising:
[0020] Weighing raw materials, wherein the raw materials, calculated by mole percentage of oxides, comprise Al2O3: 30%-55%, CaO: 25%-55%, alkaline earth metal oxide: 8%-20%, alkali metal oxide: 3%-15%, B2O3: 0%-10%, and Sb2O3: 0%-1%;
[0021] Grinding the symmetrically taken raw materials to obtain a mixed powder;
[0022] The mixed powder is melted to obtain glass liquid;
[0023] pouring glass liquid to obtain a glass precursor;
[0024] The glass precursor is annealed to obtain glass-ceramics.
[0025] According to the method for preparing glass-ceramics according to the embodiments of the present application, by introducing components such as alkali metals and alkaline earth metals into the calcium-aluminum binary system, its glass-forming properties can be improved, expanding the glass-forming region of calcium-aluminate glass to produce calcium-aluminate glass. This calcium-aluminate glass has higher mechanical strength and is more drop-resistant and scratch-resistant than traditional silicate glass and high-aluminate glass. Furthermore, the glass-melting temperature can be lowered, thereby reducing energy consumption.
[0026] As an embodiment of the second aspect of the present application, the mixed powder is melted to obtain molten glass, comprising:
[0027] The mixed powder is placed in a crucible, and the crucible is placed in a furnace and melted at 1400-1600°C for 1-3 hours to obtain glass liquid.
[0028] As an embodiment of the second aspect of the present application, pouring glass liquid to obtain a glass precursor includes:
[0029] The glass liquid is poured onto a preheated mold to obtain a uniform glass precursor.
[0030] As an embodiment of the second aspect of the present application, a glass precursor is annealed and cooled to room temperature to obtain glass-ceramics, comprising:
[0031] The glass precursor is transferred to a muffle furnace for annealing treatment. The temperature of the muffle furnace is lowered to 30-50°C below the glass transition temperature for 3-8 hours. The temperature is then lowered in steps at a cooling rate of 0.1-10°C / h, with each temperature being kept for 3-8 hours until it cools to room temperature to obtain microcrystalline glass.
[0032] As an embodiment of the second aspect of the present application, the Al2O3 is introduced as Al2O3 or Al(OH)3, the CaO is introduced as CaCO3, the alkaline earth metal oxide is introduced as alkaline earth metal carbonate, the alkali metal oxide is introduced as alkali metal carbonate, and the B2O3 is introduced as B(OH)3. As an embodiment of the second aspect of the present application, the alkaline earth metal carbonate includes one or more of MgCO3, SrCO3, and BaCO3.
[0033] As an embodiment of the second aspect of the present application, the alkaline earth metal carbonate includes MgCO3, SrCO3, and BaCO3, and the molar content of each alkaline earth metal ion is 2% to 10%. The addition of the alkaline earth metal component can effectively improve the glass-forming properties of the calcium-aluminum binary system, increase the hardness of the microcrystalline glass, and reduce the glass melting temperature and energy consumption.
[0034] As an embodiment of the second aspect of the present application, the alkali metal carbonate includes one or more of Li2CO3, Na2CO3, and K2CO3. The alkaline earth metal of this component can effectively improve the glass-forming properties of the calcium-aluminum binary system and increase the hardness of the microcrystalline glass.
[0035] As an embodiment of the second aspect of the present application, the molar percentages of the components, calculated as alkali metal oxides, are: Li2O: 1%-10%; Na2O: 2%-10%; and K2O: 0-10%.
[0036] In a third aspect, the present application further provides a glass-ceramic product, which is made of the glass-ceramic described in any one of the first aspect and its embodiments.
[0037] In a fourth aspect, the present application further provides an electronic device, comprising:
[0038] Main body middle frame;
[0039] a cover plate, the cover plate being arranged on one side of the main body middle frame; and
[0040] A display screen is provided on a side of the main body middle frame opposite to the cover plate;
[0041] Wherein, at least one of the cover plate and the display screen comprises the microcrystalline glass described in any one of the aforementioned first aspect and its embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] FIG1 is a schematic structural diagram of a mobile phone according to an embodiment of the present application;
[0043] FIG2 a is an exploded view of a mobile phone structure according to an embodiment of the present application;
[0044] FIG2 b is another structural diagram of a mobile phone according to an embodiment of the present application;
[0045] FIG3 is a scanning electron microscope photograph of the microstructure of the glass-ceramics according to one embodiment of the present application;
[0046] FIG4 is a transmittance curve diagram of a glass-ceramic according to an embodiment of the present application;
[0047] FIG5 is a flow chart of a method for preparing glass-ceramics according to an embodiment of the present application. DETAILED DESCRIPTION
[0048] The following will provide a clear and complete description of the various embodiments of the present application in conjunction with the accompanying drawings.
[0049] Nanocrystal glass, also known as ceramic glass, is an inorganic, non-metallic material that combines the properties of both glass and ceramic. While the atomic arrangement within ordinary glass is irregular, which contributes to its brittleness, nanocrystal glass, like ceramic, contains crystals whose atomic arrangement is regular. This makes nanocrystal glass brighter than ceramic and more resilient than glass.
[0050] In order to facilitate understanding of the technical solution of the present application, the technical problem of the present application is first described below.
[0051] Calcium-aluminate glass, a type of glass-ceramic, boasts superior mechanical properties compared to traditional glass. However, the glass-forming range of the calcium-aluminate binary system is very limited, occurring only when the CaO content is between 61 and 66 mol%. This results in low vitrification performance for conventional calcium-aluminate glass, limiting its application.
[0052] To address the above-mentioned technical problems, the present application provides a glass-ceramic. By introducing alkali metals and alkaline earth metals into a calcium-aluminate binary glass during the glass-ceramic preparation process, the glass-ceramic's vitrification properties are improved, expanding the vitrification region of calcium-aluminate glass, thereby producing the glass-ceramic provided herein. The glass-ceramic provided herein has higher mechanical strength and is more resistant to drops and scratches than traditional glass.
[0053] The microcrystalline glass of the present application can be applied to electronic devices. For example, the microcrystalline glass can be manufactured into cover plates of electronic devices, such as the front cover glass, back cover (back plate), etc. of mobile phone screens, as well as housings, etc.
[0054] The following describes the application scenarios of the microcrystalline glass in the embodiments of the present application by taking the application of microcrystalline glass in mobile phones as an example.
[0055] Referring to Figure 1, which shows a schematic diagram of the structure of a mobile phone according to an embodiment of the present application, the mobile phone 100 may include a back cover, a display screen, a main body frame, a camera protection cover, etc. Some or all of these components may be made of microcrystalline glass.
[0056] Referring to Figure 2a, Figure 2a shows an exploded view of the structure of part of the mobile phone in an embodiment of the present application. As shown in Figure 2a, the mobile phone 100 may include a main body middle frame 10, a back cover 20, and a display screen 30, wherein the back cover 20 and the display screen 30 are respectively arranged on both sides of the main body middle frame 10 to cover the various components arranged inside the middle frame. Among them, the display screen 30 and / or the back cover 20 can be made of microcrystalline glass. In an embodiment of the present invention, the display screen 30 and / or the back cover 20 can be made entirely of microcrystalline glass, or only partially of microcrystalline glass. In an embodiment of the present invention, the display screen 200 can be a touch screen display.
[0057] In one embodiment of the present application, as shown in Figure 2b, another schematic diagram of the structure of a mobile phone according to an embodiment of the present application is shown. A camera protection cover 21 is provided on the back cover 20 of the mobile phone 100. The camera protection cover 21 is used to cover the camera assembly to better protect the camera assembly. The camera protection cover may be made entirely or partially of the microcrystalline glass of the present application. In this embodiment of the present application, the camera protection cover is not limited to the form shown in Figure 2a.
[0058] The mobile phone of the present application adopts microcrystalline glass with excellent anti-drop performance, which makes the mobile phone resistant to falling and scratching, etc., can improve the reliability of the terminal product and enhance the user experience.
[0059] In some embodiments of the present application, the electronic device may also be a laptop computer, tablet computer, desktop computer, or other electronic device, or a smart wearable device such as a watch or bracelet, etc. The present application does not limit the type of electronic device.
[0060] In some embodiments, microcrystalline glass can also be applied to other scenarios. For example, glass parts can be used in vehicles, such as headlight covers, windshields, or dashboard glass inside the car, which can all be made of the microcrystalline glass of the present application.
[0061] In some embodiments, glass-ceramics can also be processed into glass products of different dimensions for use in different devices, for example, 2D, 2.5D, or 3D glass products. This application does not limit the application of glass-ceramics or the form of glass products.
[0062] The glass-ceramics of the embodiment of the present application will be described in detail below with reference to the accompanying drawings.
[0063] In the embodiments of the present application, the glass-ceramics includes the components shown in Table 1, in terms of molar percentage of oxides:
[0064] Table 1
[0065] In an embodiment of the present application, in a glass system containing Al2O3 and CaO, alkaline earth metal ions, such as magnesium oxide (MgO), strontium oxide (SrO), barium oxide (BaO), etc., are added to improve the glass forming ability. Glass itself is an amorphous material. When high field strength cations, such as Mg ions, are added, they attract the vacant oxygen atoms in the glass network to form a variety of tetrahedral or hexahedral structures, making the network structure tend to be compact and easier to form glass. Among them, magnesium oxide (MgO) has a relatively complex structure in the glass, and its coordination form in the glass network usually changes with the alkali metal content. Among them, the five- and six-coordinated Mg in the glass network has a similar effect to the alkali metal, and mainly plays a role in destroying the glass network structure. However, the four-coordinated Mg exists in the glass in the form of [MgO4] structural units, which can enhance the connection between the glass network formers. Strontium oxide (SrO) has important biological activity and can improve the compatibility of glass with biological cells in bioglass. Barium oxide (BaO) can mainly increase the refractive index and optical absorption of glass, and can also reduce the melting temperature of glass.
[0066] In a glass system containing Al2O3 and CaO, adding alkali metal ions can reduce the glass melting viscosity layer and improve the glass forming ability. Among them, Li2O, Na2O, and K2O are network exosomes that can reduce the glass melting viscosity layer and promote the rapid melting and clarification of the glass. In addition, Li2O and Na2O are one of the necessary components to ensure that the glass contains enough Li + 、Na + Respectively with Na in molten potassium salt + , K + The exchange occurs, generating high compressive stress on the glass surface.
[0067] Furthermore, the simultaneous addition of alkaline earth and alkali metal ions to the Al2O3 and CaO glass system can create a mixed cation effect within the existing calcium-aluminate glass, encompassing both a mixed alkali and mixed alkaline earth effect. This mixed cation effect can effectively improve the glass's forming properties and reduce melting temperatures and energy consumption.
[0068] In the embodiments of the present application, the microcrystalline glass obtained by proportioning the components according to the component contents in Table 1 can effectively improve the glass-forming properties of the glass, expand the glass-forming area of the calcium-aluminate glass, generate strong compressive stress on the glass surface, and improve the mechanical strength of the microcrystalline glass. Its drop resistance and scratch resistance are higher than those of traditional microcrystalline glass, and it can reduce the glass melting temperature and energy consumption.
[0069] In one embodiment of the present application, the alkaline earth metal oxide includes one or more of MgO, SrO, and BaO. The alkaline earth metal oxide includes at least two of these, with the molar content of each alkaline earth metal ion being 2% to 10%. This ratio can expand the glass-forming region of the calcium-aluminum binary system, thereby improving the glass-forming ability and enhancing the mechanical properties of the glass-ceramics.
[0070] In the embodiments of the present application, MgO can be introduced as MgCO3, SrO as SrCO3, and BaO as BaCO3. In some embodiments, the alkaline earth metal oxides can be introduced by other methods, such as by introducing the metal oxides themselves, such as directly introducing MgO, SrO, and BaO. The present application does not limit the introduction form of the metal oxides.
[0071] In another embodiment of the present application, the alkali metal oxide includes one or more of Li2O, Na2O, and K2O. The molar percentages of the components in the alkali metal oxide may be: the molar percentage of Li2O is between 1% and 10%. In one embodiment of the present application, the molar percentage of Li2O may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, etc.; the molar percentage of Na2O is between 2% and 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, etc.; and the molar percentage of K2O is between 0% and 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, etc.
[0072] Refer to Figure 3, which shows a scanning electron microscope photograph of the micromorphology of the microcrystalline glass of an embodiment of the present application. As shown in Figure 3, the microcrystalline glass having the above-mentioned components can obtain the nanocrystalline particles in the figure after heat treatment at different times and temperatures. The nanocrystalline particles can be one or more crystalline phases of CaAl2O4, MgAl2O4 and SrAl2O4. Among them, the particle size of the nanocrystalline particles can be from a few nanometers to hundreds of nanometers. In an embodiment of the present application, the average particle size of the nanocrystalline particles is 1-100nm, and the content of nanocrystalline can account for more than 50% of the entire microcrystalline glass. In another embodiment of the present application, the average particle size of the nanocrystalline is 1-50nm, and the content of nanocrystalline can account for more than 80% of the entire microcrystalline glass, thereby greatly improving the strength of the microcrystalline glass.
[0073] In one embodiment of the present application, the glass can be made into a transparent glass material after microcrystallization. Application of the transparent glass material to the cover glass of a mobile phone, as shown in FIG1 , can not only improve the drop resistance of the mobile phone cover but also provide a high transmittance. Application of the transparent glass material to the camera protective cover, as shown in FIG2b , can make the camera protective cover both drop-resistant and highly transmittance-effective, thereby better meeting the camera's requirements for light transmission.
[0074] Refer to Figure 4, which shows a transmittance curve for the glass-ceramics of an embodiment of the present application. As shown in Figure 4, the transmittance of the glass-ceramics of the present application can reach over 90% in the visible light range, meeting the optical requirements of electronic devices for display and photography, and is suitable for manufacturing electronic device display cover plates and camera protection cover plates.
[0075] In some embodiments, the glass may be a non-transparent material after microcrystallization. The non-transparent material may be used to make a mobile phone back panel as shown in FIG1 .
[0076] In an embodiment of the present application, a transparent glass material or a non-transparent glass material can be obtained by adjusting the components in the entire glass system. For example, when preparing a transparent glass material, 0-1 mol% of Sb2O3 can be added during the preparation of the microcrystalline glass, for example, 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.4 mol%, 0.5 mol%, 0.6 mol%, 0.7 mol%, 0.8 mol%, 0.9 mol% or 1 mol%, and the heat treatment temperature and time can be adjusted to obtain a transparent glass material. When preparing a non-transparent glass material, Sb2O3 can be omitted, and the heat treatment temperature and time can be appropriately adjusted to obtain a non-transparent glass material.
[0077] In the embodiments of the present application, B2O3 in the calcium-aluminate glass serves as a network former in the base glass. In the embodiments of the present application, the B2O3 content can be 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, or 10 mol%. This ratio can reduce the viscosity of the glass, facilitate glass production, and improve its glass-forming properties.
[0078] In some embodiments, in order to further improve the hardness of the glass-ceramics, the glass-ceramics can be subjected to low-temperature chemical strengthening (ion exchange chemical strengthening) after being produced to produce strengthened glass-ceramics. For example, the glass-ceramics can be immersed in a bath of ion exchange solution, the ion exchange solution can be sprayed onto the glass-ceramics, or the ion exchange solution can be physically applied to the glass-ceramics by any other means to bring the glass-ceramics into contact with the ion exchange solution. By subjecting the glass-ceramics to ion exchange chemical strengthening, a compressive stress layer can be formed on the surface of the glass-ceramics, thereby further improving the mechanical properties of the strengthened glass-ceramics.
[0079] In some embodiments, ion exchange chemical strengthening can be divided into multiple strengthening steps. For example, when chemical strengthening is performed twice, the temperature and time of each time can be adjusted according to different needs, thereby further improving the ion exchange depth and surface compressive stress, thereby improving the mechanical properties of the microcrystalline glass.
[0080] The preparation method of the microcrystalline glass of the present application is described below with reference to specific embodiments.
[0081] Referring to Figure 5 , a flow chart of a method for preparing glass-ceramics according to an embodiment of the present application is shown. As shown in Figure 5 , the method includes steps S510 to S540 .
[0082] S510, weigh the raw materials.
[0083] In an embodiment of the present application, the raw materials may include Al2O3 or Al(OH)3, CaCO3, carbonates of alkaline earth metals, carbonates of alkali metals, B(OH)3 and Sb2O3 raw materials. Among them, Al(OH)3 is introduced as the form of Al2O3, CaCO3 is introduced as the form of CaO, and B(OH)3 is introduced as the form of B2O3. Among them, the addition amount of each component of the raw materials is calculated as the molar percentage of the oxide, respectively, Al2O3: 30%-55%, for example, it can be 30%, 35%, 40%, 45%, 50% or 55%; CaO: 25%-55%, for example, 25%, 30%, 35%, 45%, 50% or 55%; Alkaline earth metal oxide: 8%-20%, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%; alkali metal oxides: 3%-15%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%; B2O3: 0%-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; Sb2O3: 0%-1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.
[0084] In the embodiments of the present application, Sb2O3 can be added to eliminate defects in the glass, making the glass colorless and transparent, improving the brown color problem of calcium aluminate glass, and making the glass have better transmittance, which can meet the optical requirements of display and shooting of electronic devices.
[0085] In the embodiments of the present application, adding B2O3 within 10% as defined in the present application can effectively change the glass-forming properties of the entire glass system, while appropriately reducing the viscosity of the glass, thereby solving the problem of processing being affected by excessive viscosity.
[0086] In one embodiment of the present application, the carbonate of the alkaline earth metal can be one or more of MgCO3, SrCO3, and BaCO3. That is, the carbonate of the alkaline earth metal is used as the introduction form of the alkaline earth metal oxide. When the alkaline earth metal oxide includes two or more components, the content of each alkaline earth metal ion, calculated as a molar percentage of the oxide, accounts for 2%-10% of the total amount of the raw materials, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%. The total amount of the alkaline earth metal oxide accounts for 8%-20% of the total amount of the raw materials. Such a ratio can enhance the connection between the glass network formers, thereby improving the mechanical properties of the microcrystalline glass, and can also increase the refractive index and optical absorption of the glass, reduce the glass melting temperature, and thus reduce the melting energy consumption.
[0087] In one embodiment of the present application, the alkali metal oxide comprises one or more of Li2O, Na2O, and K2O. When there are multiple alkali metal oxides, the percentage of each metal ion oxide in the total raw material is as follows: Li2O 1%-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%; Na2O 2%-10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%; and K2O 0-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%. The total content of the alkali metal oxides accounts for 3%-15% of the total raw material. This ratio can reduce the glass melt viscosity layer, promote rapid melting and clarification of the glass, generate high compressive stress on the glass surface, and improve mechanical properties.
[0088] S520, grinding the symmetrically taken raw materials to obtain a mixed powder.
[0089] The weighed raw materials are mixed and ground thoroughly to form a mixed powder.
[0090] S530, melting the mixed powder to obtain molten glass.
[0091] In an embodiment of the present application, the mixed powder can be placed in a crucible, which is then placed in a furnace and melted at 1400-1600°C for 1-3 hours to obtain molten glass. The melting temperature can be 1410°C, 1450°C, 1500°C, 1550°C, or 1600°C, and the melting time can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.
[0092] S540, pouring glass liquid to obtain a glass precursor.
[0093] In the embodiments of the present application, the molten glass can be poured onto a preheated mold to avoid excessive temperature differences that affect the glass-forming effect, thereby obtaining a transparent and uniform glass precursor.
[0094] S550, annealing the glass precursor to obtain glass-ceramics.
[0095] In one embodiment of the present application, a glass precursor is transferred to a muffle furnace for annealing at a temperature 30-50°C below the glass transition temperature (Tg). After holding the temperature for 3-8 hours, the temperature is then reduced in steps at a rate of 0.1-10°C / h, with each temperature step held for 3-8 hours. The glass precursor is then cooled to room temperature to produce a glass-ceramic. The glass-ceramic is then processed to produce a glass product. For example, the removed glass-ceramic can be processed into a glass sheet product with a thickness of 0.5-1 mm.
[0096] In one embodiment of the present application, the cooling rate can be 0.5℃ / h, 1℃ / h, 1.5℃ / h, 2℃ / h, 3℃ / h, 4℃ / h, 5℃ / h, 6℃ / h, 7℃ / h, 8℃ / h, 9℃ / h or 10℃ / h, etc.
[0097] It should be noted that when describing the microcrystalline glass above, the example ratios of the chemical components and the reasons why each chemical component can improve the glass-forming properties and mechanical properties of the microcrystalline glass have been described in detail. Please refer to the specific description of the above microcrystalline glass for details, and no further details will be given here.
[0098] In addition, the steps and methods not mentioned in this application may adopt the methods of the prior art, and this application will not describe them in detail.
[0099] The performance indicators of the microcrystalline glass in the embodiments of the present application are described below in conjunction with specific embodiments.
[0100] The implementation steps of the specific embodiment are as follows, and the specific parameter values can be referred to Table 2:
[0101] 1) Weigh the raw materials. Weigh the raw materials according to the molar percentage of the metal oxides shown in Table 2.
[0102] 2) The weighed raw materials are mixed uniformly, melted at 1600° C. for 2 hours, then cast and formed, annealed at 700° C. for 5 hours, and then cooled to room temperature at a cooling rate of 1° C. per minute to obtain calcium aluminate glass.
[0103] 3) The obtained glass precursor was processed into a glass sheet of 10 mm × 10 mm × 1 mm and polished on both sides.
[0104] 4) The calcium aluminate glass was subjected to heat treatment for microcrystallization (the heat treatment conditions of each embodiment are shown in Table 2). The Vickers hardness and Young's modulus of the glass after heat treatment were tested and are listed in Table 2.
[0105] 5) The heat-treated glass sheet is further strengthened by ion exchange. The ion exchange conditions are shown in Table 2, and the Vickers hardness of the strengthened calcium aluminate glass-ceramics is shown in Table 2. The primary ion exchange in Table 2 comprises ion exchange of the heat-treated glass in molten potassium salt.
[0106] In an embodiment, the molten potassium salt may be potassium nitrate, and the ion exchange temperature is 350°C-600°C for 0.5-3 hours. The secondary ion exchange comprises: subjecting the heat-treated glass to a first ion exchange in a first molten salt, followed by a second ion exchange in a second molten salt. The first molten salt is a mixed molten salt of potassium nitrate and sodium nitrate, and the first ion exchange temperature is 350-600°C for 0.5-3 hours; the second molten salt is potassium nitrate, and the second ion exchange temperature is 350-600°C for 0.5-3 hours.
[0107] Table 2 below is a table of parameter data corresponding to seven different embodiments using the above implementation steps.
[0108] Table 2
[0109] As can be seen from Table 2, the microcrystalline glass of the embodiment of the present application has a relatively high Vickers hardness and Young's modulus, with the Vickers hardness being between 8.4-9.1 GPa and the Young's modulus being between 110-129 GPa.
[0110] The Vickers hardness test uses the method specified in national standard GB / T 37900-2019, with a pressure of 0.1 kgf and a hold time of 10 seconds. The Young's modulus test follows the method specified in national standard GB / T 7962.6-2010.
[0111] In addition, the hardness of the microcrystalline glass in this application is compared with that of traditional silicate glass in the prior art. The same test method is used, and conventional commercial microcrystalline glass is used as a comparative example. The Vickers hardness of the glass after chemical strengthening in the comparative example is 6.3GPa, and the Young's modulus is 100GPa.
[0112] From the test results of the microcrystalline glass in Table 2 and the comparative example, it can be seen that the microcrystalline glass obtained according to the microcrystalline glass preparation method of the embodiment of the present application has a high Vickers hardness and Young's modulus, and its Vickers hardness is between 8.4-9.1GPa, and its Young's modulus is between 110-129GPa, which are much higher than the Vickers hardness and Young's modulus of the glass in the prior art.
[0113] Although the present application has been shown and described with reference to certain preferred embodiments thereof, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the application.
Claims
1. A glass-ceramic, characterized in that: Measured in mole percentage of oxides, the glass-ceramics includes the following components: Al2O3: 30%-55%; CaO: 25%-55%; Alkaline earth metal oxides: 8%-20%; Alkali metal oxides: 3%-15%; B2O3: 0%-10%; and Sb2O3:0%-1%.
2. The glass-ceramic according to claim 1, characterized in that The alkaline earth metal oxide includes one or more of MgO, SrO and BaO.
3. The glass-ceramics according to claim 1 or 2, characterized in that: The alkaline earth metal oxides include at least two of MgO, SrO and BaO, and the content of each alkaline earth metal ion is 2%-10% in mole percentage.
4. The glass-ceramic according to any one of claims 1 to 3, characterized in that The alkali metal oxide includes one or more of Li2O, Na2O and K2O.
5. The glass-ceramic according to claim 4, characterized in that: Measured by mole percentage of each component, the alkali metal oxide includes: Li2O: 1%-10%; Na2O: 2%-10%; and K2O: 0-10%.
6. The glass-ceramic according to claim 1, characterized in that: The nano-microcrystalline particles are composed of one or more crystal phases selected from the group consisting of CaAl2O4, MgAl2O4 and SrAl2O4.
7. The glass-ceramics according to claim 6, characterized in that: The average particle size of the nano-crystal particles is 1-100 nm.
8. The glass-ceramics according to claim 6 or 7, characterized in that: The content of the nano-crystal particles accounts for more than 50% of the total amount of the entire microcrystalline glass.
9. The glass-ceramics according to claim 7 or 8, characterized in that: The average particle size of the nano-crystal particles is 1-50 nm, and the content of the nano-crystal particles accounts for more than 80% of the total amount of the entire microcrystalline glass.
10. The glass-ceramic according to any one of claims 1 to 9, characterized in that: The Vickers hardness of the glass-ceramics is between 8.4 and 9.1 GPa.
11. The glass-ceramics according to any one of claims 1 to 10, characterized in that: The Young's modulus of the glass-ceramics is between 110 and 129 GPa.
12. A method for preparing glass-ceramics, characterized in that: include: Weighing raw materials, wherein the raw materials, calculated by molar percentage of oxides, comprise Al2O3: 30%-55%, CaO: 25%-55%, alkaline earth metal oxides: 8%-20%, alkali metal oxides: 3%-15%, B2O3: 0%-10%, and Sb2O3: 0%-1%; Grinding the symmetrically taken raw materials to obtain a mixed powder; Melting the mixed powder to obtain molten glass; pouring the glass liquid to obtain a glass precursor; The glass precursor is annealed and heat-treated to obtain the glass-ceramics.
13. The method according to claim 12, characterized in that The mixed powder is melted to obtain molten glass, comprising: The mixed powder is placed in a crucible, and the crucible is placed in a furnace to melt at 1400-1600° C. for 1-3 hours to obtain glass liquid.
14. The method according to claim 12, characterized in that Casting the glass liquid to obtain a glass precursor comprises: The glass liquid is poured onto a preheated mold to obtain a uniform glass precursor.
15. The method according to claim 12, characterized in that The glass precursor is subjected to annealing and heat treatment to obtain the glass-ceramics, comprising: The glass precursor is transferred to a muffle furnace for annealing treatment, wherein the temperature of the muffle furnace is lowered to between 30-50°C below the glass transition temperature, kept warm for 3-8 hours, and then cooled in steps at a cooling rate of 0.1-10°C / h, with each temperature being kept warm for 3-8 hours, until it cools to room temperature to obtain the microcrystalline glass.
16. The method according to claim 12, characterized in that The Al2O3 is introduced as Al2O3 or Al(OH)3, the CaO is introduced as CaCO3, the alkaline earth metal oxide is introduced as alkaline earth metal carbonate, the alkali metal oxide is introduced as alkali metal carbonate, and the B2O3 is introduced as B(OH)3.
17. The method according to claim 16, characterized in that The carbonates of alkaline earth metals include one or more of MgCO3, SrCO3 and BaCO3.
18. The method according to claim 17, characterized in that The alkaline earth metal carbonates include MgCO3, SrCO3 and BaCO3, and the content of each alkaline earth metal ion, calculated as a molar percentage of oxide, accounts for 2%-10% of the total raw material.
19. The method according to any one of claims 16 to 18, characterized in that: The alkali metal carbonate includes one or more of Li2CO3, Na2CO3 and K2CO3.
20. The method according to claim 18, wherein Calculated as alkali metal oxides, the molar percentages of the components are: Li2O: 1%-10%; Na2O: 2%-10%; and K2O: 0-10%.
21. A glass-ceramic product, characterized in that: The microcrystalline glass product is made of the microcrystalline glass according to any one of claims 1 to 11.
22. An electronic device, characterized in that: include: Main body middle frame; A cover plate, the cover plate being arranged on one side of the main body middle frame; as well as a display screen, the display screen being arranged on a side of the main body middle frame opposite to the cover plate; Wherein, at least one of the cover plate and the display screen comprises the microcrystalline glass according to any one of claims 1 to 11.
Citation Information
Cited By
High-strength mid-infrared wave-transparent calcium-aluminum ceramic and preparation method thereof
CN121517203A
High-strength mid-infrared wave-transparent calcium-aluminum ceramic and preparation method thereof
CN121517203B